Pemberdayaan Anak Dalam Pencegahan Anemia Di PMB Fina Sembiring Medan Tahun 2023 - Nurmalina Hutahaean; Nova Isabella Mariance Br Napitupulu; Merrygrace Simanjuntak; Enjelika Kabeakan; Feprika Yanti Munthe; Evi Safitri (STIKES Columbia Asia Medan, 2024)
This community engagement initiative aims to empower children in the prevention of anemia in PMB Fina Sembiring, Medan, in 2023. The approach involves collaboration between educational institutions, the community, and relevant stakeholders to design a child empowerment program. Concrete steps include nutritional education, the formation of children's education groups, and the development of tailored educational materials. Impact assessment is conducted to evaluate the program's effectiveness in enhancing children's knowledge of balanced nutrition, promoting dietary changes, and reducing the prevalence of anemia. The anticipated outcomes aim to contribute positively to children's health and provide a foundation for similar program planning in surrounding communities.